The Ability & Performance of Residential Urban Space A Practical Example in the City of Lattakia - Ramzy Alshaikh; Manal Salhab (Tishreen University, 2016)
يسير البحث من خلال استعراض مفهوم الفراغات العمرانية السكنية و تصنيفها, وحصر المتغيرات المؤثرة في أداء الفراغ , وتحديد طرق قياس هذه المتغيرات, ومن ثم مشاهدة ميدانية لمجموعة من الفراغات في مدينة اللاذقية , وإجراء استبيان لكل من مستخدمي الفراغات و لكل من ساكني الشرائح السكنية المؤطرة لها, بهدف التعرف إلى رأي المستخدمين في أداء الفراغ بوضعه الراهن, وتحديد أهم الاحتياجات و الأنشطة التي يفضلها المستخدم ضمن الفراغ , و أسباب اختيار فراغات معينة عن سواها. ومن ثم تحليل البيانات للوصول لنموذج رياضي يحدد أهم المتغيرات التي تؤثر سلباً أو إيجاباً في أداء الفراغ , وبناء عليه سيتم وضع آلية حول رفع أداء الفراغات العمرانية السكنية من خلال التأثير على أقوى المتغيرات المؤثرة في الفراغات ورفض المتغيرات الأضعف, ووضع توصيات لتفعيل الفراغات و جعلها بيئة تفاعل إنساني و اجتماعي و ثقافي آمن .   The paper proceeds to review the concept of Residential Urban Spaces and their classification, and to limit the variables affecting the performance of the spaces and identify the ways to measure these variables. Then, it conducts a field survey of a variety of spaces in the City of Lattakia. The paper also proceeds to conduct a questionnaire to the urban spaces users and the residents of the surrounding  segments of the population in order to identify the users' opinions and reviews on the current status of the space performance and  identify the most important needs and activities favored by the users within the space. It also identifies the reasons behind selecting certain spaces rather than others. After that, the paper proceeds to analyze the data in order to develop a mathematical model that determines the most important variables that affect the performance of the space, positively or negatively. Consequently, a mechanism will be set up to boost the performance of the Residential Urban Spaces by influencing the most powerful variables affecting the spaces and rejecting the weaker ones. Finally, making recommendations to activate the spaces and make it a safe interactive human, socio- cultural environment.